A Day at the Animal Airport - Rentta, Sharon (London Alison Green Books, 2015)
Kai the koala is going on holiday with his family. It's a very long way so they're going to fly in a plane. Kai has a wonderful time discovering all the exciting features of the airport, from using his passport, to pushing trolleys and the x-ray machine. The family just have to be careful not to miss their flight! The brand new picture book in Sharon Rentta's internationally award-winning A DAY WITH THE ANIMAL ... series is guaranteed to enchant any child who is fascinated by planes and airports.
Include Color Illustrations
Keywords: Airports -- Animals -- Children's Stories